EVALUATION OF STUDENTS' DIGITAL LITERACY SKILLS THROUGH THE USE OF A LEARNING MANAGEMENT SYSTEM - Amril, Amril (LPPM Universitas Jambi, 2026)
Digital literacy is an important competency that students must possess in facing learning and academic life in the digital era. Student digital literacy is inseparable from the use of a learning management system. This study aims to measure students' digital literacy abilities in terms of four main components: digital ethics, digital culture, digital skills, and digital security after participating in learning with a learning management system. This study uses a survey research type with a descriptive analysis design. Data were processed using the statistical application SPSS 20. The population in this study were all active students of the Faculty of Teacher Training and Education in the odd semester of 2025/2026 and the sample consisted of 75 students who had participated in learning using an online learning management system. The results showed that the overall level of student digital literacy was in the very high category (96%) and high: 4%. Each digital literacy variable was measured by six statements. Currently, there are many learning management systems circulating as a result of technological developments with various learning process features provided digitally, so that universities massively organize online learning but neglect to evaluate students' digital literacy abilities after participating in learning with a digital learning management system. This study recommends the importance of evaluating digital literacy skills as an impact of the use of technology in the learning process in higher education.